Uji Aktivitas Antibakteri Kombinasi Ekstrak Etanol 70% Daun Jarak Pagar (Jatropha curcas L.) dan Daun Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Bakteri Staphylococcus epidermidis - Chaniago, Muhamad Shadam Gusbian; Yuliana, Agnes; Paramyta, Bunga Destiyana Anggun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Staphylococcus epidermidis is a gram-positive bacterium that can cause acne. It is part of the normal flora found on the skin and is non-pathogenic. Metabolite compounds such as tannins, saponins, triterpenoids, and flavonoids present in starfruit leaves and castor leaves have antibiotic properties. The aim of this study was to determine the effectiveness of the combination of starfruit leaf extract and castor leaf extract, and to identify the most effective concentration ratio of these extracts in inhibiting Staphylococcus epidermidis bacteria. The research method used was experimental, conducting in-vitro antibacterial activity tests against Staphylococcus epidermidis. The results of the antibacterial test using a combination of starfruit leaf extract and castor leaf extract showed that at the highest ratio of 1:3, it produced an average inhibition zone of 15.73 mm against Staphylococcus epidermidis bacteria. This result was higher compared to the positive control Clindamycin HCl.